Enhancing Students' Reading Comprehension Skills through the RADEC Model: A Focus on Elementary Education - Fatimah Fatimah; Darmansyah Darmansyah; Marlina Marlina; Melva Zaini (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study proposes the utilization of the RADEC (Read, Answer, Discuss, Explain, Create) learning model, a structured approach that incorporates independent reading, collaborative discussions, peer explanations, and creative activities, as an intervention to enhance reading comprehension skills. Its objective is to investigate the impact of the RADEC learning model on the enhancement of reading abilities among fourth-grade students learning Indonesian. This study employs a non-equivalent post-test only control group design, with the experimental class using the RADEC model and the control class employing conventional teaching methods. The study included all 78 fourth-grade students from SDN 20 Kurao Pagang, divided into two classes. Random sampling yielded 22 participants in the experimental group and 23 in the control group. Data collection was conducted using evaluation tests, and the average reading comprehension scores were 82.72 for the experimental class and 63.58 for the control group. Data analysis began with initial assessments, including normality and homogeneity tests, followed by hypothesis testing using the t-test. Findings revealed a noteworthy enhancement in reading comprehension scores within the experimental group in contrast to the control group, as evidenced by a significance value of (0.000.05), indicating a statistically significant difference between the two groups. The results of this study highlight the potential of the RADEC learning model as an innovative solution for increasing students' reading interest and reading comprehension skills at the basic education level. These findings inform curriculum development, teacher training programs, and educational policies in Indonesia to enhance reading comprehension outcomes.